2014
DOI: 10.3844/ajessp.2014.74.85
|View full text |Cite
|
Sign up to set email alerts
|

Effect of With/Without Agitationof Agricultural Waste on Biogas Production From Anaerobic Co-Digestion-a Small Scale

Abstract: The growing worldwide concerns over environment, health and monetary aspects have triggered a search for efficient and economic renewable sources of energy production. Agricultural sector holds the potential for development of one of the major source of renewable energy such as biogas. In this study, CSTR-small scale fermentation (200 L stainless steel) was studied to observe the effect of stirring for natural water, cow dung, rice straw and water hyacinth ratio (2:1:1:1), which there are suitable of C: N rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…enhanced biogas production performance(Keanoi et al, 2014;Rusin et al, 2017),Yang et al (2019) did not use agitation/stirring during AD. This process could be considered more as an operational parameter of AD rather than a mechanical pretreatment strategy such as grinding or milling.…”
mentioning
confidence: 99%
“…enhanced biogas production performance(Keanoi et al, 2014;Rusin et al, 2017),Yang et al (2019) did not use agitation/stirring during AD. This process could be considered more as an operational parameter of AD rather than a mechanical pretreatment strategy such as grinding or milling.…”
mentioning
confidence: 99%
“…According to the study, the higher the viscosity, the higher the power dissipation to attain homogeneous mixing. According to Keanoi et al [67], higher biogas production was observed under mixing at higher levels of TS. Reduction in particle velocities in the vessel was observed with increasing solid content due to increased viscosity.…”
Section: Effect Of Viscosity Shear Stress and Ts Contentmentioning
confidence: 94%
“…Các nghiên cứu của Lin and Pearce (1991), Karim et al (2005)Kaparaju et al (2008) cho rằng việc khuấy trộn giúp cải thiện khí sinh học từ nhiều loại nguyên liệu khác nhau. Theo Keanoi et al (2014) việc khuấy trộn bể phân hủy chứa phân bò và chất thải nông nghiệp đã làm tăng 7,56% lượng khí sinh học. Nói chung, việc khuấy trộn giúp đạt được sự đồng nhất của chất nền và sự phân bố đồng đều các chất dinh dưỡng, pH, nhiệt độ trong bể phân hủy và giúp gia tăng năng suất sinh khí sinh học.…”
Section: Giới Thiệuunclassified